Non-linear relationships between house size and price - Feng, Shih-Tao; Peng, Chien-Wen; Yang, Chung-Hsien; Chen, Pei-Wen (International Journal of Strategic Property Management, 2021)
This study reexamines the relationship between house size and price by using the quantile regression model. Housing transactions data of the National Taipei University Special Zone in Taiwan are adopted, and the findings are as follows. First, the total price of a smaller housing unit will increase at a decreasing rate as its size increases. The decrease in marginal price might be due to the declining marginal utility of the property right. Secondly, the total price of a larger housing unit will increase at an increasing rate as its size increases. The size premium effect might be due to the influence of conspicuous consumption. Thirdly, housing with a lower square meter price is subject to greater price competitiveness in the market, and the price will increase at a decreasing rate as the size increases. Conversely, a housing unit with a higher square meter price will decrease at an increasing rate as its size increases. This might be due to the constraint imposed by the purchaser’s housing affordability. These findings clarify the nonlinear relationships between housing size and price, and provide very useful information for decision making of the developers, home purchasers, real estate appraisers, and the governments.